Evaluation of the Exterra Baiting System for the Management of Microcerotermes diversus in Baghdad Date Palm Orchards (MSW Management Journal, 2026)
Microcerotermes diversus (Silvestri) is a termite species responsible for the destruction of date palm orchards in Baghdad, Iraq. The trees are left unhealthy with low yields. This experiment was conducted to evaluate and determine the effectiveness of Exterra Baiting System comprising an insect growth regulator-chlorfluazuron in controlling termites under local field conditions. The study area comprised a date palm orchard at Abu Ghraib District containing 163 palms aged between 15-22 years old whereby all infested trees were installed with baiting stations which were monitored every 21-30 days within a period of 48 weeks checking on severity of infestation, termite activity as well as recovery of palms. In the first six weeks there was no change in levels of infestation but starting from ninth week up to thirty fifth week when finally all the palms(100%)recovered different degrees declining trends were observed. McNemar’s test showed a highly significant difference, (χ² = 158.0, df = 1, p < 0.0001), between the infestation status before and after treatment with an absolute risk reduction of 96.93%. This result supports that Exterra is significantly effective in killing termite colonies within one growing season. The baiting method attains by eliminating colonies which ensure safe-and long-lasting alternative compared to reinfestation traditional insecticide applications! Termite management strategy potential implementation emphasized study Iraq similar environments Date Palm incorporating Exterra Baiting System.